Combinação de compostos naturais e sintéticos como alternativa no controle de nematódeos gastrintestinais em pequenos ruminantes - SOUSA, : Dauana Mesquita (2023)
The parasitic load of gastrointestinal nematodes can cause financial losses in sheep and goat production. In the routine, this infection is controlled by synthetic anthelmintic compounds, such as albendazole (ABZ). However, the frequent application of these compounds accelerates the selection of resistant organisms, preventing the control of these parasites by the dose previously administered. Thus, there is a need for alternatives, such as essential oils and their terpenoids, to control gastrointestinal nematodes. These present themselves as new compounds that can be administered in combination with synthetic anthelmintics. However, knowledge about the mechanism of action of these compounds is required to develop more efficient strategies. In this context, we sought to describe the pharmacological basis of terpenes and synthetic anthelmintics combinations as an alternative to increase antiparasitic efficacy. We also gathered in a single study information on the physicochemical properties, pharmacokinetic characteristics, metabolism, and transport level of monoterpenes that may be relevant for achieving effective concentrations against different nematodes. Additionally, we evaluated the in vitro and in vivo activity of Citrus aurantium var. Dulcis essential oil (CaEO) combined with ABZ against benzimidazole-resistant Haemonchus contortus. Through in vitro egg hatch assays (EHA) using CaEO and ABZ to estimate the effective concentration to achieve 50% egg hatch inhibition (EC50) and calculate the compound combinations using a simplex-centroid mixture design. To evaluate the reduction in egg counts in feces, one group per treatment was required, with eight sheep in each. The treatments were ABZ and the combination of CaEO with ABZ. In the EHA, CaEO and ABZ presented EC50 values of 0.57 and 0.0048 mg/mL, respectively. ABZ reduced the number of eggs in the feces by 78%, however, its combination with CaEO only reduced the count by 9%. It is important to highlight that despite the in vitro efficiency, we still need to verify the possible interference caused by natural products in the metabolism of anthelmintics, and consequently, their efficacy.